Efektivitas Komunikasi Dinas Pariwisata Kota Makassar Dalam Mempromosikan Pisang Epe Sebagai Wisata Kuliner Pada Media Sosial Di Anjungan Pantai Losari - Zulqifa Muhara , Fadira; Majid , Abdul; Muttaqin , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The aims of this study were: (1) To determine the effectiveness of Makassar City Tourism Office Communications in Developing Banana Epe Culinary Tourism. (2) To find out the success of the Makassar City Tourism Office in promoting culinary tourism on banana epe social media, the losari beach pavilion. This research lasted for one month and was located in Makassar City, precisely at the Makassar City Tourism Office and Losari Beach Pavilion with as many as (6) six informants, where they are people who understand the development of banana culinary tourism in the Losati beach pavilion. The research method used is a qualitative research method, with data collection techniques carried out in two ways, namely primary data and secondary data. The data collection method is by conducting observations, interviews, documentation, literature studies and phenomenological methods. The results showed that promoting culinary tourism through banana epe social media could be said to be quite effective.